Аналіз характеристики точності відтворення еталонної траєкторії платформою Гауфа-Стюарта з системою управління для різних видів завдань - Зозуля, В. А.; Осадчий, С. І.; Мельніченко, М. М.; Зозуля, В. А.; Осадчий, С. И.; Мельниченко, Н. Н.; Zozulia, V.; Osadchy, S.; Melnichenko, M. (ЦНТУ, 2019)
Мета статті полягає в аналізі публікацій направлених на отримання оцінки точності відтворення тестового сигналу платформою Гауфа–Стюарта з певною системою керування для різних видів задач на підставі експериментальних даних. Були виявлені особливості конструкції, системи керування, типу тестового сигналу та умов експерименту, які впливають на характеристики точності платформи Гауфа–Стюарта. Цель статьи заключается в анализе публикаций направленных на получение оценки точности воспроизведения тестового сигнала платформой Гауфа-Стюарта с определенной системой управления для различных видов задач на основании экспериментальных данных. Были выявлены особенности конструкции, системы управления, типа тестового сигнала и условий эксперимента, которые влияют на характеристики точности платформы Гауфа-Стюарта. The purpose of the paper is to analyze publications aimed at obtaining an accurate estimate of the test signal reproduction by the Gough -Stewart platform with a specific control system for various types of tasks based on experimental data. At the same, to identify the features of the design, control system, type of test signal and experimental conditions that affect the accuracy characteristics of the Gough -Stewart platform. In the paper an analysis of researches on the estimation of the accuracy of the motion of the mechanism of the carrier system of the Gough -Stewart system in the dynamics was performed in the development of the reference trajectory, in particular, the circumference and the sinusoidal signal, that is, regular signals. On the basis of the analysis, the connection between the quality of the task of tracking the reference trajectory for various types of tasks performed, from the design parameters used by the control system of the Gough-Stewart platform was evaluated. As the analysis shows, the accuracy of reproduction depends on the speed of movement, and on the direction of motion. For a better evaluation of the accuracy of the control of the Gough-Stewart platform when performing a specific task, it is necessary to use as a test signal a signal that is as close as possible to the actual operating conditions. The analysis shows that used as a control system for the Gough-Stewart platform, robust and adaptive controls perform more precisely the reproduction of the trajectory than simple PD, PID. This also confirms the need for feedback that covers the entire carrier system of the Gough-Stewart platform, and not just each rod separately. It can also be seen that not one of the proposed control systems can guarantee the optimal use of the Gough-Stewart platform in order to achieve extremely precise characteristics.
Анализ характеристики точности воспроизведения эталонной траектории платформой Гауфа-Стюарта с системой управления для различных видов задач
Analysis of the Accuracy of the Reproduction of the Reference Trajectory by the Gough-Stewart Platform with the Control System for Various types of Tasks
Keywords: платформа Гауфа-Стюарта; система управління; еталонна траєкторія; оцінки точності; система управления; эталонная траектория; оценки точности; Gough-Stewart platform; control system; reference trajectory; accuracy estimates